Misfolded polypeptides are selectively recognized and transported toward aggresomes by a CED complex - Park, Joori; Park, Yeonkyoung; Ryu, Incheol; Choi, Mi-Hyun; Lee, Hyo Jin; Oh, Nara; Kim, Kyutae; Kim, Kyoung Mi; Choe, Junho; Lee, Cheolju; Baik, Ja-Hyun; Kim, Yoon Ki (Nature Publishing Group, 2017)
Misfolded polypeptides are rapidly cleared from cells via the ubiquitin-proteasome system (UPS). However, when the UPS is impaired, misfolded polypeptides form small cytoplasmic aggregates, which are sequestered into an aggresome and ultimately degraded by aggrephagy. Despite the relevance of the aggresome to neurodegenerative proteinopathies, the molecular mechanisms underlying aggresome formation remain unclear. Here we show that the CTIF-eEF1A1-DCTN1 (CED) complex functions in the surveillance of either pre-existing or newly synthesized polypeptides by linking two molecular events: selective recognition and aggresomal targeting of misfolded polypeptides. These events are accompanied by CTIF sequestration into the aggresome, preventing the additional synthesis of misfolded polypeptides from mRNAs bound by nuclear cap-binding complex. These events render cells more resistant to apoptosis induced by proteotoxic stresses. Collectively, our data provide compelling evidence for a previously unappreciated protein surveillance pathway and a regulatory gene expression network for coping with misfolded polypeptides.